Simultaneous determination of levonorgestrel and ethinyl estradiol in combined dosage form utilizing spectrophotometric methods and high performance thin layer chromatographic method on nanosilica gel plates - Rizk, Mohammed Salem; Sultan, Maha; Mohamed, Dalia; Tony, Rehab Moussa (European Journal of Chemistry, 2017)
Simultaneous quantification of levonorgestrel (LEV) and ethinyl estradiol (EE) was performed utilizing five different spectrophotometric methods and a high performance thin layer chromatographic method (HPTLC). The applied spectrophotometric methods were based on either ratio spectra namely; ratio difference, ratio subtraction and derivative ratio or the presence of isosbestic point specifically; absorbance subtraction and amplitude modulation. The proposed methods had the ability to resolve the overlapped spectra of the drugs with a linear relationship in the concentration range 1-65 µg/mL and 1-95 µg/mL for LEV and EE, respectively. The developed HPTLC method has revealed a good separation of the drugs upon utilizing Nano Silica Gel on TLC plates with fluorescent indicator 254 nm glass plates as the stationary phase and chloroform: methanol (99:1, v:v) as the mobile phase. The proposed HPTLC method has shown high sensitivity, where the linearity range was 0.02-3.00 µg/band and 0.5-20.0 µg/band, for LEV and EE, respectively. The proposed methods were successfully applied for the analysis of laboratory prepared mixtures as well as combined dosage form. Validation for all methods was conducted in compliance with the ICH guidelines proving the methods to be selective, linear, precise and accurate. The proposed methods were statistically compared with the pharmacopoeial method, where the obtained results showed no significant difference regarding accuracy and precision.